Isolation and characterization of carcinogenic chromium reducing bacillus cereus from soil of Buriganga River - Shohagh, Al Amin (Brac University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.